BPG3 is a novel chloroplast protein that involves the greening of leaves and related to brassinosteroid signaling. Issue 3 (4th March 2014) - Yoshizawa, Eriko; Kaizuka, Mai; Yamagami, Ayumi; Higuchi-Takeuchi, Mieko; Matsui, Minami; Kakei, Yusuke; Shimada, Yukihisa; Sakuta, Masaaki; Osada, Hiroyuki; Asami, Tadao; Nakano, Takeshi
Abstract: Brassinosteroids are plant steroid hormones that regulate plant organs and chloroplast development. The detailed molecular mechanism for plant development by BR signaling is yet to be revealed, and many points regarding the relationship between BR signaling and chloroplast development remain unknown. We identify here the dominant mutant Brz - insensitive - pale green3 - 1D ( bpg3 - 1D ) from the Arabidopsis FOX lines that show reduced sensitivity to the chlorophyll accumulation promoted by the BR biosynthesis inhibitor, Brassinazole (Brz), in the light. BPG3 encodes a novel chloroplast protein that is evolutionally conserved in bacteria, algae, and higher plants. The expression of BPG3 was induced by light and Brz. The inhibition of electron transport in photosystem II of the chloroplasts was detected in bpg3 - 1D . These results suggest that BPG3 played an important role in regulating photosynthesis in the chloroplast under BR signaling. Graphical abstract: : BR-inhibitor Brz activated chloroplast functions. bpg3 (Brz-insensitive-pale green3) mutant is disrupted in the signaling from BR-deficient condition to chloroplast activation.